Exploring the Dimensions of Murtadha Mutahhari's Islamic Thought Leadership and its Relevance to Freedom Learning - Arifin, Zainuddin; Alhadar, Muhdi; Gilling, Mustaming; Tohe, Ansar; Djakat, Murhim (Mudir : Jurnal Manajemen Pendidikan, 2023)
This research focuses on analyzing the works of Murtadha Muthahhari’s thoughts that are relevant to freedom of learning. The independent learning system that occurs in Indonesia requires a comprehensive concoction so that all levels of education from early childhood to higher education can carry out the learning process, especially in Islamic education. The method that the author uses is the library research method with a qualitative descriptive approach. The approach by describing in full and in detail about the issue of actual and social phenomena that occur and are experienced and practiced by Muthahhari in his life and life, and supported by some data from the journal imliyah. The results obtained in this study conclude that Murtadha Muthahhari's thought has an important relevance in independent learning. His autonomous, critical and open approach can strengthen the spirit of free and continuous search for knowledge in Muslim societies. By adopting Muthahhari's thinking, education can be a means to strengthen faith and a deeper understanding of Islam, while remaining open and appreciative of different views and thoughts in an increasingly complex world.